Stress-dependent growth in breast cancer arises from a mechano-osmotic coupling and cell-sizing checkpoint - Irish Senthilkumar; Jef Vangheel; Vatsal Kumar; Laoise McNamara; Bart Smeets; Enda Howley; Eoin McEvoy (Proceedings of the National Academy of Sciences, 2026)
Mechanoresponsive cell proliferation is a feature of growing tumors, despite the suppression of many other regulatory checkpoints in cancer, but the underlying cell-scale mechanisms driving this behavior have not yet been established. In this study, we propose a biophysical model for cell growth as governed by actively controlled osmolarity, which we integrate with a discrete particle framework to simulate growth and remodeling of breast cancer spheroids. Confinement and biomechanical feedback from the extracellular environment are analyzed through a neural-network-accelerated finite element solver. Combining the framework with experiments, our model reveals that stress-dependent spheroid growth can arise from a sizing checkpoint for mitosis. Under sufficient extracellular loading, cell growth is restricted by high hydrostatic forces in competition with osmotic pressure from biomolecule synthesis, which prevents cells from surpassing a critical volume. Our model provides insight into mechanosensitive growth arrest in breast cancer, potentially serving as a computational tool for analyzing growth in a wider range of normal and malignant biological tissues.